Short term performance of bonus issue announcement on Malaysian public listed firms / Nurshawal Othman - Othman, Nurshawal (2013)
This present study examines the stock price reaction to the information content of bonus issues with a view of examining the Malaysian stock market is semi-strong efficient or not. The period of the study is January 2005 until December 2007 including 85 samples of firms that announcing bonus issue. The present study used the event study methodology in order to examine the impact of bonus issues announcement on share prices. Results revealed that Average Abnormal Return (AAR) is positive at 0.15%. But, the bonus issue announcements have insignificant impact on share price on announcement day while the result of Cumulative Abnormal Return (CAR) is 22.98% and statistically significant at 1% level. Based on the findings, it shows that there is delay market reaction happened and semi-strong market does not efficient but provides stronger evidence on signaling hypothesis